Edukasi pencegahan stunting di Desa Sukamaju Kecamatan Sidomulyo Lampung Selatan - Ningsih, Tri Riwayati (JOURNAL OF Public Health Concerns, 2024)
Background: Stunting is a form of failure in child growth and development due to chronic malnutrition. One third of toddlers in Indonesia have below average height. The number of stunted children in Indonesia is ranked fifth in the world. To achieve the target of reducing stunting rates, changes in community behavior are needed. Purpose: The community service carried out by KKN 160 in an effort to prevent stunting is in collaboration with PKK mothers, village midwives and Sukamaju village officials. Method: The stunting prevention activities carried out in Sukamaju Village are a form of Community Service in an effort to prevent stunting. The programs implemented are in the form of education, providing PMT in the form of sweet corn, tempeh and spinach, and providing prenagen milk for pregnant women. Using interactive lecture methods, collaboration and demonstrations. Education in the form of stunting counseling with the theme "Together Prevent Stunting Healthy and Strong Children Great Generation", TPK assistance by measuring Body Length (PB) or Height (TB) and Body Weight (BB), and serving a healthy menu. Results: Through this activity, the community or participants who attended have begun to understand and understand stunting. In this activity, all participants were also given the opportunity to discuss and ask questions about the material. The activity was also attended by all participants with enthusiasm because they felt that the presentation of the material was very useful for all participants in order to recognize whether or not family members were experiencing stunting so that they could take preventive measures and take action to check themselves with health workers or report to related parties, especially to the village office or related parties. Participants can re-explain the material presented. Conclusion: Education about stunting has a positive impact on local residents. Efforts to prevent stunting through education or socialization, providing additional food (PTM) and providing prenagen milk for pregnant women as well as weighing and measuring the weight of toddlers in order to provide direct knowledge and understanding of stunting. Community service activities carried out were able to increase the knowledge of the target of the activity about the problem of short toddlers (stunting) so that it was followed by an increase in awareness that was owned according to the target of the activity regarding the problem of short toddlers (stunting). Suggestion A series of activities carried out in community service in the "Together Preventing Stunting Healthy and Strong Children Great Generation" Program were continued by the village such as posyandu cadres and could be a proposal for activities for the village. The reason this activity needs to be maintained and continued is because it is known that this activity is successful at least in increasing the knowledge and awareness of the target of the activity, but it must be carried out continuously in order to create behavioral changes and prevent stunting. Keywords: Great generation; Healthy children; Prevention; Stunting Pendahuluan: Stunting merupakan salah satu bentuk kegagalan dalam tumbuh kembang anak akibat kekurangan gizi kronis. Sepertiga anak balita di Indonesia memiliki tinggi badan di bawah rata-rata. Jumlah anak stunting di Indonesia menduduki peringkat kelima di dunia. Untuk mencapai target penurunan angka stunting diperlukan perubahan perilaku masyarakat. Tujuan: Pengabdian yang dilakukan KKN 160 dalam upaya pencegahan stunting ini bekerja sama dengan ibu-ibu PKK, bidan desa dan perangkat desa Sukamaju. Metode: Kegiatan pencegahan stunting yang dilakukan di Desa Sukamaju merupakan salah satu bentuk Pengabdian Kepada Masyarakat dalam upaya pencegahan stunting. Program yang dilaksanakannya berupa edukasi, pemberian makanan sehat berupa sayur jagung manis, tempe dan bayam, serta pemberian susu prenagen untuk ibu hamil. Menggunakan metode ceramah interaktif, kolaborasi dan demonstrasi. Edukasi berupa penyuluhan stunting dengan tema " Bersama Cegah Stunting Anak Sehat Dan Kuat Generasi Hebat “, pendampingan TPK dengan mengukur Panjang Badan (PB) atau Tinggi Badan (TB) dan Berat Badan (BB), serta penyajian menu sehat. Hasil: Melalui kegiatan ini masyarakat atau peserta yang hadir sudah mulai mengerti dan paham tentang stunting, Pada kegiatan ini juga di berikan kesempatan untuk seluruh para peserta berdiskusi serta tanya jawab tentang materi tersebut. Kegiatan pun di ikuti oleh seluruh peserta dengan antusias karena merasa pemaparan materi sangat bermanfaat bagi seluruh peserta untuk mengenali bahwa anggota keluarga ada yang mengalami stunting atau tidak agar bisa melakukan pencegahan serta melakukan tindakan untuk memeriksakan diri pada tenaga kesehatan atau melaporkan pada pihak terkait khususnya pada pihak apart desa atau pihak terkait. Peserta dapat menjelaskan ulang dari materi yang disampaikan. Simpulan: Edukasi tentang stunting memberikan dampak positif bagi warga setempat. Upaya pencegahan stunting dengan edukasi atau sosialisasi, pemberian makanan tambahan dan pemberian susu prenagen ibu hamil serta penimbangan dan pengukuran berat badan pada anak balita agar dapat memberikan pengetahuan dan pemahaman secara langsung terhadap stunting. Kegiatan pengabdian kepada masyarakat yang dilakukan mampu meningkatkan pengetahuan sasaran kegiatan tentang masalah balita pendek (stunting) sehingga diikuti oleh peningkatan awareness yang dimiliki sesuai sasaran kegiatan terhadap masalah balita pendek (stunting). SARAN Serangkaian kegiatan yang dilakukan dalam pengabdian kepada masyarakat dalam Program “ Bersama Cegah Stunting Anak Sehat Dan Kuat Generasi Hebat “ dilanjutkan oleh pihak desa seperti kader posyandu dan dapat menjadi usulan kegiatan bagi desa. Alasan kegiatan ini perlu dipertahankan dan dilanjutkan karena sudah diketahui bahwa kegiatan ini berhasil setidaknya untuk meningkatkan pengetahuan dan awareness sasaran kegiatan, namun harus dilakukan secara berkelanjutan agar dapat menciptakan perubahan perilaku dan mencegah terjadinya stunting.